Catch Them When They Fall - Tau'au-Filisi, Helen Fa'amotu (Auckland University of Technology, 2012)
In 1991, Ela returns to teach at Southside High school as a first year English teacher in Otara, South Auckland after a seven year absence in tertiary study. She too had been schooled in South Auckland schools in Mangere and initially wanted to return back to Uni after two years of teaching to complete a PhD, write fiction and poetry, and then find a nice man to marry but nothing has quite prepared her for the challenges that she must face at Southside High. She meets her students': Ben, a developing artist and 'gentle giant' who is on his own learning journey, who is missing his mum and lives with his dad; Ruth, an aspiring student who wants to study law and faces family difficulties; Ruth's best friend Moana, who is an inspiring singer and wants to be a future teacher but has to make some difficult choices and Moana's ex-boyfriend Jackson, 'the big mouth' and trouble maker who faces some difficulties of his own. She also meets Lani, a 'sleeping' teacher who has become disillusioned with teaching who challenges Ela about what she can do to make a difference. 'Catch them when they Fall,' are their stories of courage, frailties, hopes and dreams in a world where it seems as if everything is going against them.
Keywords: Education; South Auckland